From Diverse Origins to Specific Targets: Role of Microorganisms in Indirect Pest Biological Control - Frédéric Francis (Insects, 2020)
Integrated pest management (IPM) is today a widely accepted pest management strategy to select and use the most efficient control tactics and at the same time reduce over-dependence on chemical insecticides and their potentially negative environmental effects. One of the main pillars of IPM is biological control. While biological control programs of pest insects commonly rely on natural enemies such as predatory insects, parasitoids and microbial pathogens, there is increasing evidence that plant, soil and insect microbiomes can also be exploited to enhance plant defense against herbivores. In this mini-review, we illustrate how microorganisms from diverse origins can contribute to plant fitness, functional traits and indirect defense responses against pest insects, and therefore be indirectly used to improve biological pest control practices. Microorganisms in the rhizosphere, phyllosphere and endosphere have not only been shown to enhance plant growth and plant strength, but also promote plant defense against herbivores both above- and belowground by providing feeding deterrence or antibiosis. Also, herbivore associated molecular patterns may be induced by microorganisms that come from oral phytophagous insect secretions and elicit plant-specific responses to herbivore attacks. Furthermore, microorganisms that inhabit floral nectar and insect honeydew produce volatile organic compounds that attract beneficial insects like natural enemies, thereby providing indirect pest control. Given the multiple benefits of microorganisms to plants, we argue that future IPMs should consider and exploit the whole range of possibilities that microorganisms offer to enhance plant defense and increase attraction, fecundity and performance of natural enemies.